(untitled) (International Journal of Physiology, 2019)
Background Menstrual hygiene is an issue that is very important among adolescent females and mother is the best teacher and also school teachers play an important role in the menstrual hygiene practices and it is also important aspect of Millennium Development Goals (MDGs). Objectives To identify the socio demographic profile factors and to know the menstrual problems among the study population. Materials & Method A cross sectional institutional based study was conducted at International Indian School, Buraidah from January 2014 to May 2014 among the school children from 5th Class to 9th class. A total of 240 children data collected and classes selected randomly from the female sections. Data was entered in MS excel and necessary statistical tests were applied. Results Out 240 adolescents, about 207 (86.2%) children are attained menarche. Out of 207 adolescent students, about 29% were attained menarche at 10 years of age group and 16.6% of female students at 13 years of age group. There was statistically significant association was found between literacy of the mother and menstruation in the female school children. Out of 207 adolescents, about 45.8% were having pre menstrual syndrome symptoms. about 73.4% (152/207) were having normal BMI and 26.6% were having abnormal BMI. Conclusions The pre-menstrual symptoms and the menstrual problems were quite commonly prevailing in this age group and as it is Indian school and students from different geographical, socioeconomic background and different cultures and ethnic. Proper awareness programme has to be implemented periodically to address for the common menstrual problems which occurs in adolescent age group.